Effect of host and environment related factors on the distribution of the ectoparasites of the montane grass mouse Akodon montensis (Cricetidae, Sigmodontinae) in the Atlantic Forest ecoregion in northeastern Argentina - Mara Urdapilleta; Carlos A. Galliari; Tomás Navarro-Febre; Marcela Lareschi (Revista Mexicana de Biodiversidad)
Akodon montensis is dominant in the Urugua-í Provincial Park in northeastern Argentina. We analyse the effect of variables related to the hosts and the environment on the parasitic burden (PB), and specific richness and mean abundance of Laelapidae mites (Mesostigmata) (SL, MAL). PB, SL and MAL were used with the logarithm transformed data in the analysis. One-way ANOVA was used to test differences between rodents of different sex in an exploratory analysis, and the Levene test was then used to confirm the homogeneity of variances. Using the same technique, differences in these parameters were tested between the states of sexual maturity. To test the effect of trapped site and its interaction with the sex of the rodent on MAL and SL, a two-way ANOVA was performed. The PAST software was used. The results support that the sex of the host would be the main factor that modulates PB and MAL, but not SL. The size and weight of the hosts (as a proxy for age), the reproductive stage and site of capture of the rodents, would not affect any of the variables analysed. The results obtained contribute to the comprehension of the epidemiological role of laelapids.